Comparative study on α-decay of ground and isomeric states of Bi isotopes using improved semi-empirical relationship & modified GLDM - Jose, Tinu Ann; Santhosh, K. P. (Indian journal of physics, 2025)
We have improved the SemFIS formula by Poenaru et al. (Phys Rev C 74: 014312, 2006), including the effect of angular momentum and a systematic study on alpha decay half-life of ground and isomeric states of 184−224 Bi ( Z = 83) is investigated. We further refined the modified SemFIS by Akrawy et al. (Nucl Phys A 1021: 122419, 2022) eliminates its drawbacks in reproducing experimental data on bismuth isotopes, and the improved SemFIS models show higher accuracy in predicting alpha decay half-life. Also, alpha decay half-life is predicted using the Modified Generalized Liquid Drop Model (MGLDM), its improved version with new preformation parameters and other empirical formulas. Among all models, the New Geiger-Nuttall law demonstrates the lowest standard deviation. We hope our predictions will contribute to further experimental inquiries in this domain.